Memahami Lifeworld Anak Yatim Dhuafa : Studi Fenomenologi Komunikasi Pengasuhan dan Konstruksi Makna di Yayasan Pundi Amal Bakti Ummat - Ailsa Iftinah Bahy; Zainal Abidin; Ema Ema (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Drawing on the participants' concrete lived experiences, this study explores how the processes of typification and we-relations shape the construction of meaning in everyday interactions. Data were collected through in-depth interviews and participant observation with four informants and one single caregiver, and analyzed descriptively texturally and structurally. The findings show that affective communication includes empathy, humor, and firm but authoritative correction that become the foundation for the formation of emotional bonds and a sense of “new family.” Holistic routines (praying in congregation, studying, social activities) facilitate the internalization of religious values, discipline, and independence, which in turn strengthen children's self-identity. The process of meaning construction does not only occur through words, but through daily practices that bring together the emotional, spiritual and social dimensions. These results recommend strengthening intersubjective communication training for caregivers in similar institutions to support the development of character and identity of orphans.